Peran Pengasuh Panti Asuhan Membentuk Karakter Disiplin dalam Meningkatkan Kecerdasan Intrapersonal Anak - A. Mustika Abidin (Institut Agama Islam Negeri (IAIN) Bone-Indonesia, 2018)
This article shows the role of caregiver of orphanage to form the character of discipline in improving children intrapersonal intelligence. The orphanage is a social institution that has a service program that is provided to answer the needs of the community in order to deal with social problems, especially the problems of poverty, stupidity and the problems of orphans, abandoned children who grow in the community. With the role of caregiver of the orphanage is to provide services based on the profession of social work to children who do not have a father or mother (orphan) or both (orphans) as a substitute for parents by loving, helping and guiding (nursing, preserving, and educating) the child is expected to form the character of discipline so as to improve the intrapersonal intelligence of the child (the intelligence in himself to recognize and understand himself).